Makna Hutan Bagi Masyarakat Adat Kajang, Suatu Kearifan Lokal dalam Pelestarian Lingkungan - Jumrana . (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2013)
ABSTRACT The meaning of forests for kajang indigenous awning is a source of life, the link with the creator, and a sacred place to perform various ceremonies. Therefore it is very necessary to be preserved. Referring to the patuntung philosophy of life is written in the passang, these indigenous people live simply and wisely treated woods, taking a little of the forest and use just enough to live. The knowledge that the forests will keep the water flowing, springs remain, and drought disasters can be avoided is the knowledge gained over generations and passed down through cultural communication. Key words: Kajang ethnicgroup, local wisdom, forest